Effects of Organomontmorillonite Content on Morphology and Mechanical and Thermal Properties of Poly(2, 6-dimethyl-1, 4-phenylene oxide)/Polyamide-66 Nanocomposites. (11th October 2016) - Yang, Kunxiao; Xin, Chunling; Huang, Ying; Jiang, Lilong; He, Yadong
Abstract : The nanocomposites consisting of polymer matrix and nanofiller have attracted great attention because of the improved physical properties. In this paper, organomontmorillonite (OMMT) was introduced into poly(2, 6-dimethyl-1, 4-phenylene oxide) grafted maleic anhydride (PPO-g-MA) compatibilized poly(2, 6-dimethyl-1, 4-phenylene oxide)/polyamide-66 (PPO/PA66) blends by melt extrusion. The morphology of PPO/PA66 nanocomposites with different amounts of OMMT was investigated using transmission electron microscopy (TEM), wide-angle X-ray diffraction (WAXD), and scanning electron microscopy (SEM). The OMMT platelets exhibited an exfoliated structure in the PA66 matrix and an intercalated structure on the surface of PPO domains at low OMMT loading (2 phr). However, the exfoliated platelets in matrix were found to transform into intercalated stacks by adding 6 phr of OMMT. The mechanical properties and thermal stability were significantly improved with the coexistence of exfoliated and intercalated OMMT at low OMMT loading (2–4 phr). The exfoliated OMMT platelets imposed a confinement effect on the macromolecular chains and thereby increased the storage modulus and complex viscosity of nanocomposites.